Green low-carbonic acid uranium leaching tailing filling material and preparation method thereof
By using uranium tailings, gelling materials, lime, slump retainer and water in uranium tailings filling materials, the problems of severe acid reflux, low early strength, severe later deterioration and disintegration, environmental pollution caused by nuclide release and migration, low utilization rate and high cost of uranium tailings are solved, and efficient and stable filling effects and low-cost uranium tailings are achieved.
Patent Information
- Application Number
- CN202411727173.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing uranium tailings filling materials have severe acid reflux, low early strength, serious deterioration and disintegration in the later stage, environmental pollution caused by nuclide release and migration, and low utilization rate and high cost of uranium tailings.
The combination of uranium tailings, gelled materials, lime, slum retention agent and water is adopted. The cemented materials include cement clinker, phosphorus slag powder, slag powder and silicon fume. Through specific mixing steps, the synergistic effect between raw materials is maximized, which inhibits acid reflux of uranium tailings, improves the strength and stability of the filler, and effectively controls the release and migration of nuclides.
Significantly inhibit acid reflux of uranium tailings, improve the early and later strength and stability of the filling, reduce costs, improve the solid waste utilization rate of uranium tailings, and effectively control the release and migration of nuclides, and reduce environmental pollution.
Smart Images

Figure BDA0005159477380000111 
Figure BDA0005159477380000131 
Figure BDA0005159477380000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mine filling and low-radioactive solid waste disposal, and in particular to a green low-carbonic acid leaching uranium tailings filling material and a preparation method thereof. Background Art
[0002] Uranium tailings are a large volume of solid waste produced after uranium is extracted from hard rock uranium mines using the surface acid method. A large amount of sulfuric acid and long-lived radioactive nuclides remain in the uranium tailings, which are very harmful. Under the background of "dual carbon", the global peaceful use of nuclear energy is accelerating, the demand for natural uranium is growing, and the total amount of uranium tailings emissions continues to increase, making mines face more severe environmental protection and safety pressures.
[0003] At present, the disposal of uranium tailings is mainly based on surface tailings pond storage. In the process of stacking, not only a large amount of land is occupied, but also the release and migration of hazardous elements in the uranium tailings into water bodies, soil and atmosphere will pose a threat to the ecological environment and human health. At the same time, the tailings pond faces high maintenance and governance costs during service and after retirement. In addition, solidification and stabilization is also a method for disposing uranium tailings. Patent document CN117383901A discloses a uranium tailings curing agent and a curing method thereof. The curing material used is composed of mineral powder, sodium silicate, river sand, uranium tailings and water. The uranium tailings solidified body obtained by this method has the characteristics of high strength and stable performance. However, the mass ratios of cementitious material to aggregate, mineral powder to sodium silicate in this method are 1:1~3 and 2~5:1 respectively. There are problems such as low utilization rate of uranium tailings, high consumption of activator, high curing cost, large land occupation and cumbersome daily maintenance, which are difficult to implement in production.
[0004] In recent years, cementing filling technology based on tailings and other mining solid waste has been widely used in mines at home and abroad. This technology can make full use of uranium tailings as "waste" to control the potential "three disasters" of uranium mine goaf collapse, tailings dam breach and surface environmental pollution. It has the advantages of low cost, high tailings utilization rate and environmental friendliness, making large-scale utilization of uranium tailings possible. Ordinary Portland cement is the most commonly used filling cementitious material in mines, but because uranium tailings are completely soaked in sulfuric acid, sulfuric acid will be slowly released for a long time in a humid environment. The filling body prepared with uranium tailings and cement has abnormally serious acid reflux, and there are problems such as low early strength of the filling body, severe degradation and disintegration in the later stage, and high risk of nuclide release and migration. Therefore, the development of a green, low-carbon, high-efficiency, low-cost uranium tailings filling material and preparation method for filling mine goafs is of great significance to the reduction of large industrial solid wastes such as low-radioactive uranium tailings, pollution control and sustainable development and utilization of uranium resources. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a green low-carbonic acid leaching uranium tailings filling material and a preparation method thereof, aiming to solve the problems of existing uranium tailings filling materials such as severe acid reflux, low early strength, severe degradation and disintegration in the later stage, environmental pollution caused by nuclide release and migration, low utilization rate and high cost of uranium tailings.
[0006] In a first aspect, the embodiment of the present application provides a green low-carbonic acid leaching uranium tailings filling material, characterized in that it includes uranium tailings, a cementitious material, lime, a collapse-preventing agent and water; wherein the cementitious material includes, by mass percentage:
[0007] 30-40% cement clinker, 60-70% phosphorus slag powder;
[0008] Alternatively, 15-50% cement clinker, 30-80% phosphorus slag powder, 0-15% slag powder and 0-10% silica fume.
[0009] In the technical solution of the embodiment of the present application, the superposition effect produced by the reaction of the superior and inferior components of multi-source active solid waste and uranium tailings can not only inhibit the acid reflux of uranium tailings, greatly improve the strength and later stability of the filling body, and reduce costs, but also effectively control the release and migration of radioactive nuclides. The utilization rate of uranium tailings solid waste in the filling material of the present application is high, and the solid waste content in the cementitious material is large, the value is low, and the source is wide, which is conducive to the low-carbon, green, and low-cost production of uranium mines and has good application prospects.
[0010] In some embodiments, the uranium tailings are solid waste after uranium is extracted using a sulfuric acid leaching agent in a surface heap leaching process or a stirring leaching process, and have a pH value of 3.5 to 4.5 and a maximum particle size of ≤10 mm.
[0011] In this embodiment, the uranium tailings are soaked in sulfuric acid and a large amount of soluble uranium remains. When used as filling aggregate, SO4 2- It will slowly seep out for a long time, and the SO4 2- A large amount of Ca can be released by cement clinker and lime in water 2+ OH - The reaction produces gypsum.
[0012] In some embodiments, the phosphorus slag powder is a powder ground from granulated electric furnace phosphorus slag, with a specific surface area of ≥300m 2 / kg, 28d activity index ≥85%, P2O5 content ≤5%, and radioactive indicators IRa and Ir are both ≤1.
[0013] In this embodiment, on the one hand, when preparing the filling slurry, the residual phosphoric acid in the phosphorus slag powder is dissolved and reacts with the soluble nuclides in the uranium tailings to form insoluble minerals, thereby achieving chemical fixation of the nuclides and reducing the risk of uranium leaching and migration from the source. On the other hand, the newly formed Ca(OH)2 and gypsum in the filling material destroy the Si-O-Si bond, Al-O-Si bond, and Al-O-Al bond on the surface of the phosphorus slag powder glass, causing it to slowly release [SiO4] 4- 、[AlO4] 5- etc., and with Ca 2+ It combines to form hydrated calcium silicate and hydrated calcium aluminate, and the hydrated calcium aluminate further reacts with gypsum to produce ettringite; this process mainly occurs in the middle and late stages of hydration, and its function is to consume the gypsum and Ca(OH)2 produced by the uranium tailings filling material in the middle and late stages, inhibit the acid reflux of uranium tailings, reduce the gypsum content, increase the amount and performance of hydrated calcium silicate, and enhance the strength and stability of the filling body in the middle and late stages. At the same time, the secondary physical fixation and stabilization of the nuclides is achieved through the adsorption and encapsulation of the hydration products.
[0014] In some embodiments, the slag powder is a powder ground from granulated blast furnace slag, with a specific surface area of ≥400m 2 / kg, 28d activity index ≥95%, SO3 content ≤4%, and radioactive indicators IRa and Ir are both ≤1.
[0015] In this embodiment, the activity of slag powder is higher than that of phosphorus slag powder. After adding slag powder, the newly formed Ca(OH)2 and gypsum in the filling material break the Si-O-Si bond, Al-O-Si bond, and Al-O-Al bond on the surface of the slag powder glass body, releasing [SiO4] 4- 、[AlO4] 5- etc., and with Ca 2+ Combined to form hydrated calcium silicate and hydrated calcium aluminate, hydrated calcium aluminate reacts with gypsum to produce ettringite. This process mainly occurs in the early and middle stages of hydration, and its function is to produce more hydrated calcium silicate and ettringite in the early and middle stages of hydration, thereby improving the early and middle strength of the filling body. The synergistic effect of slag powder and phosphorus slag powder reduces the total amount of gypsum and Ca(OH)2 in the filling material, which can weaken the corrosion of sulfate on the filling body, improve the full-age strength and stability of the filling body, and at the same time further enhance the fixation and stabilization of nuclides.
[0016] In some embodiments, the silicon ash specifically refers to the powder collected in the flue during the smelting of ferrosilicon alloy, with a specific surface area of ≥15000m 2 / kg, activity index ≥105%, SiO2 content ≥85%.
[0017] In this embodiment, the activity of silica fume is higher than that of slag powder. After adding silica fume, the newly generated Ca(OH)2 in the filling material destroys the Si-O-Si bond on the surface of the silica fume glass, causing it to quickly release [SiO4]. 4- , and with Ca 2+ Combined to form hydrated calcium silicate. This process mainly occurs in the early stage of hydration, and its function is to produce more hydrated calcium silicate in the early stage of hydration, thereby improving the early strength of the filling body and the density of the matrix. The addition of silica fume will increase the early hydration products in the filling body, which can enhance its blocking effect on the original crack channels on the surface of uranium tailings particles, prevent free water from entering the interior of uranium tailings particles, and inhibit SO4 2- It releases and reduces the formation of gypsum in the middle and late stages. At the same time, the synergistic effect with phosphorus slag powder and slag powder enhances the full-age strength and stability of the filling body and the fixation and stabilization of nuclides.
[0018] In some embodiments, the specific surface area of the cement clinker is 300 to 400 m 2 / kg, the mass percentage of silicate minerals is greater than 66%.
[0019] In this embodiment, C3S, C2S, and C3A in cement clinker dissolve a large amount of Ca(OH)2, [SiO4] 4- 、[Al(OH)4] - etc., part of Ca(OH)2 consumes SO4 dissolved in uranium tailings 2- Gypsum is produced. The new gypsum slows down the hydration reaction of cement clinker and is used to reduce the slump loss of filling slurry. C3S in cement clinker hydrates before C2S to form hydrated calcium silicate. At the same time, the new gypsum reacts with C3A to form calcium aluminate. The filling material begins to solidify and form strength. The remaining Ca(OH)2 and new gypsum create conditions for the continuous hydration reaction of phosphorus slag powder, slag powder or silica fume in the filling material, promoting its hydration to produce more hydrated calcium silicate, etc.
[0020] In some embodiments, the lime is quicklime powder, with a CaO content of ≥90%, and an added amount of 0.08-0.15% of the dry weight of the uranium tailings.
[0021] In this embodiment, lime dissolves a large amount of Ca(OH)2 when it comes into contact with water, and part of the Ca(OH)2 reacts with a large amount of SO4 dissolved in the initial stage of the uranium tailings. 2- The reaction generates gypsum, and the remaining Ca(OH)2 provides an alkaline environment and calcium source for the hydration of phosphate slag powder, slag powder or silica fume, ensuring the continuation of the hydration reaction of phosphate slag powder, slag powder or silica fume.
[0022] In some embodiments, the collapse retaining agent includes: a high-efficiency water reducing agent and / or a high-performance water reducing agent; the high-efficiency water reducing agent includes one or more of aminosulfonate, naphthalene series, anthracene series, melamine resin, and ketone-aldehyde condensation product high-efficiency water reducing agent; the high-performance water reducing agent includes a polycarboxylic acid high-performance water reducing agent; and the addition amount of the collapse retaining agent is 0.2 to 0.8% of the mass of the cementitious material.
[0023] In this embodiment, on the one hand, the collapse-preserving agent is used to improve the fluidity of the filling slurry, reduce the unit water consumption in the filling material, and reduce the segregation and water bleeding rate of the filling slurry. At the same time, the free water content in the filling body is greatly reduced after the water consumption is reduced, so that the SO4 2- The release is more difficult, and the acid regurgitation of uranium tailings is suppressed. On the other hand, the total amount of new gypsum in the filling body is reduced, and the hydration reaction of the cementitious material synergistically improves the full-age strength, stability and fixation and stabilization of nuclides of the filling body.
[0024] In a second aspect, the present application provides a method for preparing a green low-carbonic acid leaching uranium tailings filling material, comprising the following steps:
[0025] S1. Mix uranium tailings, phosphorus slag powder and water, stir thoroughly to obtain a mixed slurry;
[0026] S2. Add cement clinker, slag, silica fume, lime and collapse-preventing agent to the mixed slurry in sequence, stir thoroughly and obtain uranium tailings filling material.
[0027] In the technical solution of the embodiment of the present application, the uranium tailings are firstly uniformly stirred with water, and the sulfur-containing clay minerals on the surface of the uranium tailings are washed away with water to make the particle surface smoother, and the SO4 on the surface of the uranium tailings particles is dissolved to the maximum extent in the pulping process. 2- , so that the slurry forms an acidic environment. In addition, the soluble uranium in the uranium tailings particles can be dissolved to the maximum extent. Then add phosphorus slag powder. The residual phosphoric acid in the phosphorus slag powder can mineralize soluble uranium and other nuclides under weakly acidic conditions, maximizing the chemical fixation efficiency of soluble uranium and other nuclides; then add cement clinker, slag powder, silica fume, lime, and collapse inhibitor in turn. During the stirring process, a large amount of Ca(OH)2 and [SiO4] 4- 、[Al(OH)4] - etc., part of Ca(OH)2 consumes SO4 dissolved in uranium tailings 2- Gypsum is produced; at the same time, C3S and C3A in the cement clinker undergo hydration reaction, and the filling material begins to solidify and form strength; the remaining Ca(OH)2 and new gypsum create conditions for the continuous hydration reaction of phosphate slag powder, slag powder or silica fume in the filling material, promote their hydration to produce more products such as hydrated calcium silicate, so as to improve the strength and later stability of the filling body.
[0028] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0029] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.
[0031] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0032] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0033] In order to solve the problems of serious acid reflux of existing cement uranium tailings filling bodies, low early strength, serious degradation and disintegration in the later stage, environmental pollution caused by the release and migration of nuclides, low utilization rate and high cost of uranium tailings, the present application provides a green low-carbonic acid leaching uranium tailings filling material and its preparation method. The filling materials in the present application include: uranium tailings, cement clinker, phosphorus slag powder, slag powder, silica fume, collapse inhibitor and water. The present invention adopts multi-source active solid waste as the main component of the filling cementitious material, which can not only inhibit the acid reflux of uranium tailings, greatly improve the strength and later stability of the filling body, and reduce the cost, but also effectively control the release and migration of radioactive nuclides; the uranium tailings solid waste utilization rate in the filling material of the present application is high, and the solid waste in the cementitious material is of low value and wide source, which can realize the low-carbon and environmentally friendly disposal of uranium tailings, and has good application prospects.
[0034] On the one hand, the embodiment of the present application provides a green low-carbonic acid leaching uranium tailings filling material, including uranium tailings, a cementitious material, lime, a collapse retaining agent and water; the total mass of the uranium tailings, the cementitious material and the lime accounts for 77-83% of the mass of the uranium tailings filling material, and the mass ratio of the cementitious material to the uranium tailings is 1:4-1:25; wherein the cementitious material, calculated by mass percentage, includes:
[0035] 30-40% cement clinker, 60-70% phosphorus slag powder;
[0036] Alternatively, 15-50% cement clinker, 30-80% phosphorus slag powder, 0-15% slag powder and 0-10% silica fume.
[0037] In the technical solution of the embodiment of the present application, the superposition effect produced by the reaction of the superior and inferior components of multi-source active solid waste and uranium tailings can not only inhibit the acid reflux of uranium tailings, greatly improve the strength and later stability of the filling body, and reduce costs, but also effectively control the release and migration of radioactive nuclides. The utilization rate of uranium tailings solid waste in the filling material of the present application is high, and the solid waste content in the cementitious material is large, the value is low, and the source is wide, which is conducive to the low-carbon, green, and low-cost production of uranium mines and has good application prospects.
[0038] Furthermore, in some embodiments, the cementitious material includes, by mass percentage, 15-50% of cement clinker, 30-80% of phosphorus slag powder, and 5-15% of slag powder.
[0039] In the technical solution of the embodiment of the present application, the slag powder releases a large amount of [SiO4] under the action of Ca(OH)2 and gypsum. 4- 、[AlO4] 5- etc., and with Ca 2+ Combined to form hydrated calcium silicate and hydrated calcium aluminate, hydrated calcium aluminate reacts with gypsum to produce calcium aluminate. This process mainly occurs in the early and middle stages of hydration, and can make up for the low strength of the filling body in the early and middle stages. In addition, the synergistic effect of slag powder and phosphorus slag powder reduces the total amount of gypsum and Ca(OH)2 in the filling material, which can weaken the corrosion of sulfate on the filling body, improve the full-age strength and stability of the filling body, and at the same time further enhance the stable fixation of nuclides.
[0040] Furthermore, in some embodiments, the cementitious material includes, by mass percentage, 15-50% of cement clinker, 30-80% of phosphorus slag powder, and 3-10% of silica fume.
[0041] In the technical solution of the embodiment of the present application, silica fume rapidly releases [SiO4] under the action of Ca(OH)2. 4- , and with Ca 2+Combined to form hydrated calcium silicate. This process mainly occurs in the early stage of hydration, making up for the low early strength of the filler and improving the density of the matrix. In addition, hydrated calcium silicate blocks the original crack channels on the surface of uranium tailings particles, preventing free water from entering the interior of uranium tailings particles, inhibiting SO4 2- It releases and reduces the formation of gypsum in the middle and late stages. The synergistic effect with phosphorus slag powder enhances the full-age strength, stability of the filling and the stable fixation of radionuclides.
[0042] Furthermore, in some embodiments, the cementitious material includes, by mass percentage, 15-50% of cement clinker, 30-80% of phosphorus slag powder, 5-10% of slag powder and 3-10% of silica fume.
[0043] In the technical solution of the embodiment of the present application, the addition of slag powder can react with Ca(OH)2 and gypsum to produce hydrated calcium silicate and hydrated calcium aluminate. The hydrated calcium aluminate reacts with gypsum to produce calcium aluminate, thereby improving the early and middle-term strength of the filling body. The added silica fume can react with Ca(OH)2 to produce a large amount of hydrated calcium silicate in the early stage, thereby improving the early strength and density of the filling body. The synergistic effect of the two and the phosphorus slag powder enhances the full-age strength, stability and fixation and stabilization of the nuclides of the filling body.
[0044] Furthermore, in some embodiments, the uranium tailings are solid waste after uranium is extracted using a sulfuric acid leaching agent in a surface heap leaching process or a stirring leaching process, and the pH value thereof is 3.5 to 4.5, and the maximum particle size is ≤10 mm.
[0045] In the technical solution of the embodiment of the present application, the uranium tailings are soaked with sulfuric acid and a large amount of soluble uranium remains. When used as filling aggregate, SO4 2- It will slowly seep out for a long time, and the SO4 2- Ca2+ can be released from cement clinker and lime in water 2+ OH - Produces large amounts of gypsum.
[0046] Furthermore, in some embodiments, the phosphorus slag powder is a powder ground from granulated electric furnace phosphorus slag, with a specific surface area of ≥300m 2 / kg, 28d activity index ≥85%, P2O5 content ≤5%, and radioactive indicators IRa and Ir are both ≤1.
[0047] In the technical solution of the embodiment of the present application, on the one hand, when preparing the filling slurry, the residual phosphoric acid in the phosphorus slag powder is dissolved and reacts with the soluble nuclides in the uranium tailings to form insoluble minerals, thereby achieving chemical fixation of the nuclides and reducing the risk of uranium leaching and migration from the source. On the other hand, the newly formed Ca(OH)2 and gypsum in the filling material destroy the Si-O-Si bonds, Al-O-Si bonds, and Al-O-Al bonds on the surface of the phosphorus slag powder glass, causing it to slowly release [SiO4]4- 、[AlO4] 5- etc., and with Ca 2+ It combines to form hydrated calcium silicate and hydrated calcium aluminate, and the hydrated calcium aluminate further reacts with gypsum to produce ettringite; this process mainly occurs in the middle and late stages of hydration, and its function is to consume the gypsum and Ca(OH)2 produced by the uranium tailings filling material in the middle and late stages, inhibit the acid reflux of uranium tailings, reduce the gypsum content, increase the amount and performance of hydrated calcium silicate, and enhance the strength and stability of the filling body in the middle and late stages. At the same time, the secondary physical fixation and stabilization of the nuclides is achieved through the adsorption and encapsulation of the hydration products.
[0048] Furthermore, in some embodiments, the slag powder is a powder ground from granulated blast furnace slag, with a specific surface area of ≥400m 2 / kg, 28d activity index ≥95%, SO3 content ≤4%, and radioactive indicators IRa and Ir are both ≤1.
[0049] In the technical solution of the embodiment of the present application, the activity of slag powder is higher than that of phosphorus slag powder. After adding slag powder, the newly formed Ca(OH)2 and gypsum in the filling material break the Si-O-Si bond, Al-O-Si bond, and Al-O-Al bond on the surface of the slag powder glass body, releasing [SiO4] 4- 、[AlO4] 5- etc., and with Ca 2+ Combined to form hydrated calcium silicate and hydrated calcium aluminate, hydrated calcium aluminate reacts with gypsum to produce ettringite. This process mainly occurs in the early and middle stages of hydration, and its function is to produce more hydrated calcium silicate and ettringite in the early and middle stages of hydration, thereby improving the early and middle strength of the filling body. The synergistic effect of slag powder and phosphorus slag powder reduces the total amount of gypsum and Ca(OH)2 in the filling material, which can weaken the corrosion of sulfate on the filling body, improve the full-age strength and stability of the filling body, and at the same time further enhance the fixation and stabilization of nuclides.
[0050] Furthermore, in some embodiments, the silica ash specifically refers to the powder collected in the flue during the smelting of ferrosilicon alloy, with a specific surface area of ≥15000m 2 / kg, activity index ≥105%, SiO2 content ≥85%.
[0051] In the technical solution of the embodiment of the present application, the activity of silica fume is higher than that of slag powder. After adding silica fume, the newly generated Ca(OH)2 in the filling material destroys the Si-O-Si bond on the surface of the silica fume glass, causing it to quickly release [SiO4] 4- , and with Ca 2+Combined to form hydrated calcium silicate. This process mainly occurs in the early stage of hydration, and its function is to produce more hydrated calcium silicate in the early stage of hydration, thereby improving the early strength of the filling body and the density of the matrix. The addition of silica fume will increase the early hydration products in the filling body, which can enhance its blocking effect on the primary crack channels on the surface of uranium tailings particles, prevent free water from entering the interior of uranium tailings particles, and inhibit SO4 2- It releases and reduces the formation of gypsum in the middle and late stages. At the same time, the synergistic effect with phosphorus slag powder and slag powder enhances the full-age strength and stability of the filling body and the fixation and stabilization of nuclides.
[0052] Furthermore, in some embodiments, the specific surface area of cement clinker is 300-400m 2 / kg, the mass percentage of silicate minerals is greater than 66%.
[0053] In the technical solution of the embodiment of the present application, C3S, C2S, and C3A in cement clinker dissolve a large amount of Ca(OH)2 and [SiO4] 4- 、[Al(OH)4] - etc., part of Ca(OH)2 consumes SO4 dissolved in uranium tailings 2- Gypsum is produced. The new gypsum slows down the hydration reaction of cement clinker and is used to reduce the slump loss of filling slurry. C3S in cement clinker hydrates before C2S to form hydrated calcium silicate. At the same time, the new gypsum reacts with C3A to form calcium aluminate. The filling material begins to solidify and form strength. The remaining Ca(OH)2 and new gypsum create conditions for the continuous hydration reaction of phosphorus slag powder, slag powder or silica fume in the filling material, promoting its hydration to produce more hydrated calcium silicate, etc.
[0054] Furthermore, in some embodiments, the lime is quicklime powder, the CaO content is ≥ 90%, and the added amount is 0.08-0.15% of the dry weight of the uranium tailings.
[0055] In the technical solution of the embodiment of the present application, in this embodiment, lime dissolves a large amount of Ca(OH)2 when it meets water, and part of the Ca(OH)2 and the large amount of SO4 dissolved in the initial stage of the uranium tailings 2- The reaction generates gypsum, and the remaining Ca(OH)2 provides an alkaline environment and calcium source for the hydration of phosphate slag powder, slag powder or silica fume, ensuring the continuation of the hydration reaction of phosphate slag powder, slag powder or silica fume.
[0056] Furthermore, in some embodiments, the collapse retaining agent includes: a high-efficiency water reducing agent and / or a high-performance water reducing agent; the high-efficiency water reducing agent includes one or more of aminosulfonate, naphthalene series, anthracene series, melamine resin, and ketone-aldehyde condensation product high-efficiency water reducing agent; the high-performance water reducing agent includes a polycarboxylic acid high-performance water reducing agent; and the addition amount of the collapse retaining agent is 0.2 to 0.8% of the mass of the cementitious material.
[0057] In the technical solution of the embodiment of the present application, in this embodiment, on the one hand, the collapse retaining agent is used to improve the fluidity of the filling slurry, reduce the unit water consumption in the filling material, and reduce the segregation and water bleeding rate of the filling slurry. At the same time, after the water consumption is reduced, the free water content in the filling body is greatly reduced, so that the SO4 2- The release is more difficult, and the acid regurgitation of uranium tailings is suppressed. On the other hand, the total amount of new gypsum in the filling body is reduced, and the hydration reaction of the cementitious material synergistically improves the full-age strength, stability and fixation and stabilization of nuclides of the filling body.
[0058] In a second aspect, the present application provides a method for preparing a green low-carbonic acid leaching uranium tailings filling material, comprising the following steps:
[0059] S1. Mix uranium tailings, phosphorus slag powder and water, stir thoroughly to obtain a mixed slurry;
[0060] S2. Add cement clinker, slag, silica fume, lime and collapse-preventing agent to the mixed slurry in sequence, stir thoroughly and obtain uranium tailings filling material.
[0061] In the technical solution of the embodiment of the present application, the uranium tailings are firstly uniformly stirred with water, and the sulfur-containing clay minerals on the surface of the uranium tailings are washed away with water to make the particle surface smoother, and the SO4 on the surface of the uranium tailings particles is dissolved to the maximum extent in the pulping process. 2- , so that the slurry forms an acidic environment. In addition, the soluble uranium in the uranium tailings particles can be dissolved to the maximum extent. Then add phosphorus slag powder. The residual phosphoric acid in the phosphorus slag powder can mineralize soluble uranium and other nuclides under weakly acidic conditions, maximizing the chemical fixation efficiency of soluble uranium and other nuclides; then add cement clinker, slag powder, silica fume, lime, and collapse inhibitor in turn. During the stirring process, a large amount of Ca(OH)2 and [SiO4] 4- 、[Al(OH)4] - etc., part of Ca(OH)2 consumes SO4 dissolved in uranium tailings 2- Gypsum is produced; at the same time, C3S and C3A in the cement clinker undergo hydration reaction, and the filling material begins to solidify and form strength; the remaining Ca(OH)2 and new gypsum create conditions for the continuous hydration reaction of phosphate slag powder, slag powder or silica fume in the filling material, promote their hydration to produce more products such as hydrated calcium silicate, so as to improve the strength and later stability of the filling body.
[0062] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0063] Example 1
[0064] This embodiment provides a green low-carbonic acid leaching uranium tailings filling material and a preparation method thereof, which specifically includes the following steps:
[0065] (1) Weigh the required raw materials according to the following weight proportions: 1000 parts of uranium tailings, 25.03 parts of cement clinker, 60.52 parts of phosphorus slag powder, 10.04 parts of slag, 4.95 parts of silica fume, 1 part of lime, 0.4 parts of polycarboxylic acid, and 274 parts of water;
[0066] (2) Put the weighed uranium tailings and phosphorus slag powder into a mixer, then slowly add the weighed water, and stir at a stirring rate of 80 r / min for 1 min;
[0067] (3) Then, the weighed cement clinker, slag, silica fume, lime and polycarboxylic acid are slowly added in sequence and stirred at a stirring rate of 80 r / min for 3 min to obtain uranium tailings filling slurry.
[0068] Among them, the sources and performance parameters of each raw material are as follows:
[0069] Uranium tailings are solid waste produced after uranium is extracted by sulfuric acid leaching agent in heap leaching process. They are provided by a hard rock uranium mine heap leaching field. The pH value is 4.5, the moisture content is 9%, the particle size distribution is shown in Table 1, and the chemical composition is shown in Table 2.
[0070] Table 1 Particle size distribution of uranium tailings
[0071]
[0072] Table 2 Chemical composition of uranium tailings
[0073] Element <![CDATA[SiO2]]> CaO <![CDATA[Al2O3]]> <![CDATA[K2O]]> <![CDATA[SO3]]> <![CDATA[Fe2O3]]> <![CDATA[Na2O]]> MgO <![CDATA[U3O8]]> content / % 68.92 3.43 7.52 2.03 1.98 1.05 0.32 0.51 0.013
[0074] Cement clinker is provided by Hunan Conch Cement Co., Ltd. with a density of 3046kg / m 3 , with a specific surface area of 400m 2 / kg, the mass percentage of silicate minerals is 79.87%.
[0075] Phosphorus slag powder was obtained from a phosphorus chemical enterprise in Weng'an, Guizhou, with a density of 2828kg / m 3 , with a specific surface area of 306m 2 / kg, mass coefficient is 1.32, basicity coefficient is 1.19, activity index is 88.5%, P2O5 content is 4.6%, and radioactive indexes IRa and Ir are both ≤1.
[0076] The slag powder is S95 grade slag provided by Wuhan Weishen Technology Development Co., Ltd., with a density of 2876kg / m 3, with a specific surface area of 408m 2 / kg, mass coefficient is 2.01, SO3 content is 2.42%, alkalinity coefficient is 1.07, activity index is 98%, and radioactive indicators IRa and Ir are both ≤1.
[0077] Silica fume is provided by Henan Borun New Materials Co., Ltd., with a specific surface area of 20150m 2 / kg, the activity index is 110%, and the SiO2 content is 96.25%.
[0078] The collapse-preventing agent is a polycarboxylic acid water-reducing agent; the CaO content in the lime powder is 95%.
[0079] Examples 2 to 9 and Comparative Examples 1 to 5
[0080] Examples 2 to 9 and Comparative Examples 1 to 5 respectively provide a green low-carbonic acid leaching uranium tailings filling material and a preparation method thereof. Compared with Example 1, the difference is that the ratios of cement clinker, phosphorus slag powder, slag and silica fume in the filling cementitious material are different, and the specific amounts are shown in Table 3. The other steps are roughly the same as those in Example 1 and are not repeated here.
[0081] Table 3 Content of each component in the cementitious material in Examples 2 to 9 and Comparative Examples 1 to 5
[0082] Example / Comparative Example Cement clinker (unit) Phosphorus slag powder (parts) Slag (parts) Silica fume (parts) Example 2 26.3 63.2 10.5 0 Example 3 23.7 56.8 9.5 10 Example 4 27.8 66.7 0 5.5 Example 5 23.5 56.5 15 5 Example 6 15 70 10 5 Example 7 25.6 61.4 8 5 Example 8 30 70 0 0 Example 9 40 60 0 0 Comparative Example 1 23 53 9 15 Comparative Example 2 23.1 54 20 2.9 Comparative Example 3 5 85 6.7 3.3 Comparative Example 4 80 20 0 0 Comparative Example 5 20 80 0 0
[0083] Comparative Example 6
[0084] This comparative example provides a green low-carbonic acid leaching uranium tailings filling material and a preparation method thereof. Compared with Example 1, the difference is that no polycarboxylic acid collapse retaining agent is added, and the other steps are substantially the same as those in Example 1, which will not be repeated here.
[0085] Comparative Example 7
[0086] The comparative example provides a green low-carbonic acid leaching uranium tailings filling material and a preparation method thereof. Compared with Example 1, the difference lies in that the filling material preparation steps are different, that is, uranium tailings, cement clinker, phosphorus slag powder, slag, silica fume, lime and polycarboxylic acid are put into a mixer together, and then water is slowly added, and stirred at a stirring rate of 80r / min for 5min to obtain uranium tailings filling slurry. The other steps are substantially the same as those in Example 1 and will not be repeated here.
[0087] Comparative Example 8
[0088] The comparative example provides a green low-carbonic acid leaching uranium tailings filling material and a preparation method thereof. Compared with Example 1, the difference is that the cementitious material is 42.5# ordinary Portland cement; the uranium tailings filling material preparation steps are: weighing raw materials in proportion, putting uranium tailings, 42.5# ordinary Portland cement, and lime into a mixer, and then slowly adding water, stirring at a stirring rate of 80r / min for 5min to obtain uranium tailings filling slurry, and the other steps are substantially the same as those in Example 1, which will not be repeated here.
[0089] Among them, the source and performance parameters of 42.5# ordinary Portland cement are as follows:
[0090] 42.5# cement is provided by Hunan Conch Cement Co., Ltd., with a density of 2956kg / m 3 , with a specific surface area of 364m 2 / kg.
[0091] The water seepage rate, slump and diffusion of the filling slurry in Examples 1 to 9 and Comparative Examples 1 to 8 were tested according to the "Test Method for Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016); and the setting time of the filling slurry was tested according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T 70-2009). The test results are shown in Table 4.
[0092] Table 4 Performance test results of filling slurry in Examples 1 to 9 and Comparative Examples 1 to 8
[0093]
[0094]
[0095] The filling slurry in Examples 1 to 9 and Comparative Examples 1 to 8 was poured into a cylindrical test mold with a size of φ50 mm × H100 mm. After solidification and demoulding, the filling body test block was placed in a curing box for curing (humidity of 95%, temperature of 20°C). The uniaxial compressive strength of the filling body test block was tested according to the "Technical Standard for Metal and Non-metal Mining Filling Engineering" (GB / T 51450-2022) at 7d, 28d, 90d and 180d, respectively. The test results are shown in Table 5.
[0096] Table 5 Strength test results of filling bodies in Examples 1 to 9 and Comparative Examples 1 to 8
[0097]
[0098]
[0099] The occurrence forms of uranium in the filling bodies at the ages of 7d, 28d and 90d in Examples 1 to 9 and Comparative Examples 1 to 8 were analyzed by a step-by-step continuous extraction test. Then, the nuclide leaching test was carried out on the filling body specimens cured for 28d according to the Standard Leaching Test Method for Solidified Low- and Intermediate-Level Radioactive Wastes (GB / T7023-2011), and the leaching rate and leaching fraction of uranium in the filling body were calculated. The test results are shown in Table 6.
[0100] Table 6 Test results of uranium leaching and radon precipitation in filling bodies in Examples 1 to 9 and Comparative Examples 1 to 8
[0101]
[0102]
[0103] The solid waste content and material cost in the filling materials in Examples 1 to 9 and Comparative Examples 1 to 8 are shown in Table 7.
[0104] Table 7 Solid waste content and material cost in filling materials in Examples 1 to 9 and Comparative Examples 1 to 8
[0105]
[0106] It can be seen from Table 4 that the bleeding rates of Examples 1 to 9 are all between 1.5% and 5%, the slump is greater than 25 cm, the setting time is greater than 8 hours, and the filling slurry has good stability and fluidity; compared with Example 1, the bleeding rate and slump of Comparative Example 1 are relatively small, and the setting time of Comparative Example 1 and Comparative Example 4 is relatively small, which is not conducive to pipeline transportation; the bleeding rate and setting time of Comparative Example 3 and Comparative Example 5 are relatively large, and the bleeding rate of Comparative Example 6 is relatively large, and the filling slurry has poor stability. The slump of Comparative Example 6 is relatively low, and long-distance pipeline transportation cannot be achieved; it means that the raw materials of the cementitious material include 30-40% cement clinker and 60-70% phosphorus slag powder by mass percentage; or, when the raw materials include 15-50% cement clinker, 30-80% phosphorus slag powder, 0-15% slag powder and 0-10% silica fume, the filling slurry can meet the production requirements, and the filling material with raw materials exceeding this range will have different degrees of performance problems.
[0107] It can be seen from Table 5 that the strength of Examples 1 to 9 gradually increases with time, and the stability in the later stage is good; the strength of Comparative Example 8 increases first and then decreases with time, and obvious deterioration occurs at 180 days. The 28d strength of Examples 1 to 9 is greater than 2.8MPa, the 90d strength is greater than 4MPa, and the 180d strength is higher than 5MPa, which are 1.57 to 2.5, 1.81 to 2.22, and 2.89 to 3.49 times that of Comparative Example 8, respectively. It can be seen that the strength and stability of the filling material made of the raw materials of the present application are significantly better than those of ordinary cement uranium tailings filling materials. The 7d strength of Examples 1 to 7 is significantly higher than that of Examples 8 to 9, indicating that the addition of slag and silica fume can significantly improve the early strength of the filling slurry.
[0108] It can be seen from Table 5 and Table 7 that compared with Example 1, the strength of each age of Comparative Examples 1 to 3 decreased significantly, among which the strength of Comparative Example 3 decreased most significantly, the shrinkage and cracking of Comparative Example 2 was more obvious, and the cost of Comparative Example 1 was the highest. Compared with Example 1, the strength of Comparative Example 7 at each stage was lower, indicating that the order of adding, mixing and stirring the materials had a certain influence on the strength. Compared with Example 8, the 7d strength of Comparative Example 4 increased by 107%, and the 28-180d strength decreased by 6.5-37.3%, while the cost was 1.54 times that of Example 8; compared with Example 9, although the cost of Comparative Example 5 was the lowest, its strength decreased by 34.4-47.5%; so considering the comprehensive cost and the performance requirements for filling slurry in actual production, the ratio of cement clinker and phosphorus slag powder in the cementitious material raw materials in the filling slurry of this application is relatively reasonable.
[0109] It can be seen from Table 6 that the uranium leaching rate, leaching fraction and mobile uranium content in Examples 1 to 9 are much lower than those in Comparative Example 8. Compared with Example 1, the uranium leaching rate, leaching fraction and mobile uranium content in Comparative Example 7 increased by 2.67, 2.82 and 1.06 times, respectively. It can be seen that the filling material obtained by the raw material ratio and preparation method provided by the present invention has a better effect on the fixation and stabilization of uranium than the filling material obtained by the conventional raw material and preparation method, and the uranium leaching rate and migration risk are at a lower level.
[0110] As shown in Table 7, the solid waste content in the uranium tailings filling material in Examples 1 to 9 is higher than 96%, which is much higher than that in Comparative Example 8. While having excellent performance, it is beneficial to the reduction of bulk industrial solid waste and energy conservation and carbon reduction. The average cost of raw materials in Examples 1 to 9 is 42.32 yuan / m 3 , which is significantly lower than that of Comparative Examples 1, 4 and 8. Therefore, the uranium tailings filling material provided by the present invention has good economic efficiency.
[0111] In summary, the present application provides a green low-carbonic acid leaching uranium tailings filling material and a preparation method thereof, which belongs to the field of mine filling technology and the field of low-radioactive solid waste disposal technology. The filling materials in the present application include: uranium tailings, cementitious materials, lime, collapse retaining agents and water, wherein the cementitious materials include: cement clinker, phosphorus slag powder, slag powder, silica fume; and then the raw materials are mixed through specific steps to maximize the synergistic effect between the raw materials, so that the fixation of the nuclides and the strength of the filling materials are maximized. (1) The uranium tailings filling material prepared by the present invention has good fluidity, low water seepage rate, and moderate coagulation time, which can meet the transportation requirements; the early strength of the filling body is adjustable and controllable, the mid- and late-stage strength is high, and the stability is good; the filling body has excellent fixation and control effects on nuclides; the comprehensive performance of the uranium tailings filling material is far better than that of cement uranium tailings filling material, and has good application prospects. (2) The filling material of the present invention makes full use of the superposition effect of the reaction between active solid waste and superior and inferior components in uranium tailings, chemically fixes the nuclides from the source through the residual phosphoric acid in the phosphorus slag, and uses the active components in the phosphorus slag powder, slag powder or silica ash to consume the newly formed Ca(OH)2 and gypsum in the hydration process, which can inhibit the acid regurgitation of uranium tailings and greatly improve the strength, later stability and anti-leaching property of nuclides of the filling body. (3) The total solid waste content in the solid of the uranium tailings filling material of the present invention exceeds 96%, which can consume a large amount of bulk industrial solid waste such as uranium tailings, effectively alleviate the stacking pressure of the tailings pond and the surface environmental pollution, and reduce the maintenance cost and decommissioning cost of the uranium tailings pond. (4) The solid waste content in the filling cementitious material provided by the present invention is large, the source is wide, and the value is low. While effectively improving the performance of the filling body, it greatly reduces the filling cost and can also reduce CO2 emissions, which is beneficial to reducing costs and increasing efficiency in hard rock uranium mining and promoting "double carbon" work.
[0112] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A green low-carbonic acid leaching uranium tailings filling material, characterized in that: It includes uranium tailings, cementitious materials, lime, collapse-preventing agents and water; wherein, the cementitious materials, calculated by mass percentage, include: 30-40% cement clinker, 60-70% phosphorus slag powder; Alternatively, 15-50% cement clinker, 30-80% phosphorus slag powder, 0-15% slag powder and 0-10% silica fume.
2. The green low-carbonic acid leaching uranium tailings filling material according to claim 1 is characterized in that: The uranium tailings are solid wastes after uranium is extracted by using sulfuric acid as a leaching agent in a surface heap leaching process or a stirring leaching process, and the pH value thereof is 3.5 to 4.5, and the maximum particle size is ≤10 mm.
3. The green low-carbonic acid leaching uranium tailings filling material according to claim 1 is characterized in that: The phosphorus slag powder is a powder ground from granulated electric furnace phosphorus slag, with a specific surface area of ≥300m 2 / kg, 28d activity index ≥85%, P2O5 content ≤5%, and radioactive indicators IRa and Ir are both ≤1.
4. The green low-carbonic acid leaching uranium tailings filling material according to claim 1 is characterized in that: The slag powder is a powder ground from granulated blast furnace slag, with a specific surface area of ≥400m 2 / kg, 28d activity index ≥95%, SO3 content ≤4%, and radioactive indicators IRa and Ir are both ≤1.
5. The green low-carbonic acid leaching uranium tailings filling material according to claim 1 is characterized in that: The silica ash refers to the powder collected in the flue during the smelting of ferrosilicon alloy, with a specific surface area of ≥15000m 2 / kg, activity index ≥105%, SiO2 content ≥85%.
6. The green low-carbonic acid leaching uranium tailings filling material according to claim 1, characterized in that: The specific surface area of the cement clinker is 300-400m 2 / kg, the mass percentage of silicate minerals is greater than 66%.
7. The green low-carbonic acid leaching uranium tailings filling material according to claim 1 is characterized in that: The lime is quicklime powder, with a CaO content of ≥90%, and an added amount of 0.08-0.15% of the dry weight of the uranium tailings.
8. The green low-carbonic acid leaching uranium tailings filling material according to claim 1, characterized in that: The slump-retaining agent includes: a high-efficiency water reducing agent and / or a high-performance water reducing agent; the high-efficiency water reducing agent includes one or more of aminosulfonate, naphthalene series, anthracene series, melamine resin, and ketone-aldehyde condensation product high-efficiency water reducing agents; the high-performance water reducing agent includes a polycarboxylic acid high-performance water reducing agent; and the addition amount of the slump-retaining agent is 0.2 to 0.8% of the mass of the cementitious material.
9. A method for preparing a green low-carbonic acid leaching uranium tailings filling material, characterized in that: The following steps are involved: S1. Mix uranium tailings, phosphorus slag powder and water, stir thoroughly to obtain a mixed slurry; S2. Add cement clinker, slag, silica fume, lime and collapse-preventing agent to the mixed slurry in sequence, stir thoroughly and obtain uranium tailings filling material.
Citation Information
Patent Citations
Low-bleeding-rate pumpable phosphogypsum and yellow phosphorus slag filling paste and preparation method of paste
CN103964804A
Treatment method of radioactive solid waste
CN111145931A
Uranium-containing wastewater treatment agent and method for treating uranium-containing wastewater
CN113461133A
Uranium tailing curing agent and curing method thereof
CN117383901A
Low-alkali hydraulic material
JP2000143326A